Examining the Mediating Influence of Green Behavior on the Impact of Green HR Practices on Environmental Sustainability - Ali, Muhammad Ramzan; Iqbal, Syed Muhammad Javed; Farhan, Muhammad Ahsan-u-llah (iRASD Journal of Management, 2022)
It is the main purpose of this research to investigate the mediating role of employees' green behavior in the relationship between green HR practices (including green hiring, green compensation, and green training) and environmental sustainability in organizations. Quantitative poll data provided the basis for this investigation. Questionnaires played a crucial role in this study. The study's sample group consisted of workers from the multinational corporations Nestle, Uniliver, Haier, and a number of software development firms in Pakistan. After the events of Covid-19, researchers made an effort to gather 336 responses from participants. The data was gathered from companies doing business in Pakistan using a combination of random and handy sampling techniques. Descriptive statistics (mean, rates, and standard deviation) were calculated in SPSS version 23 and inferential statistics were calculated using Smart PLS version 3.0. In this study, we investigated the relationship between green HR practices and environmental sustainability by testing thirteen hypotheses; ten were found to have substantial support, while the other three did not. This study contributes significantly to the existing body of literature by proposing a paradigm that can play a pivotal part in increasing an organization's commitment to environmental sustainability. This study contributes to the literature by examining how green HRM can change the attitudes and actions of workers to become more environmentally conscious. The context of this research is Pakistani society. This research explores the connection between environmental consciousness and green human resource practices in the Pakistani workforce.